Do Subjective Norms Have a Role on Intentions to Implement Whistleblowing with Self Efficacy as a Moderating Variable? (Study on Bachelor of Accounting Students at the University of Mataram) - Baiq Aprilia Dita Suwandi; Ayudia Sokarina (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the effect of attitude variables, subjective norms, and behavioral control on the intention to apply whistleblowing with self-efficacy as a moderating variable in Bachelor of Accounting students at the University of Mataram. This study used a quantitative method with a questionnaire data collection technique. Questionnaires were distributed to 257 respondents consisting of accounting students in 2018, 2019 and 2020. The data analysis technique in this study was Moderating Regression Analysis (MRA). The results showed that attitude and behavioral control had a significant effect on the intention to apply whistleblowing, while subjective norms did not have a significant effect. Self efficacy has the potential to moderate the influence of attitudes, subjective norms, and behavioral control on the intention to implement whistleblowing. Thus, self-efficacy does not significantly moderate the effect of attitudes, subjective norms, and behavioral control on the intention to implement whistleblowing.